Analisa Detak Jantung dengan Metode Heart Rate Variability (HRV) untuk Pengenalan Stres Mental Berbasis Photoplethysmograph (PPG) - Nefy Puteri Novani; Lathifah Arief; Rima Anjasmara (Universitas Andalas, 2019)
Emotions influence individual behavior and there is no emotional experience that has a stronger influence than stress. Prolonged stress has a direct negative influence on physical and emotional conditions. For that reason, it is important to know a person's mental stress state, so that further action can be taken later, so as not to have a serious impact on physical and mental health. In this study, the photoplethysmograph (PPG) approach is used to recognize mental stress conditions based on Heart Rate Variability (HRV) frequency domain analysis. In this study stress was identified by SVM classifier using LF, HF and LF / HF Ratio from HRV frequency domain analysis. The LF results were increased in mild stress conditions, HF increased in conditions of mild stress and medium stress and the LF / HF Ratio slowly increased from mild stress to severe stress. The training data obtained 80 data with 95% mild stress accuracy from 19 data, medium stress accuracy 96% from 49 data and 99% severe stress accuracy with 12 data.